2018
DOI: 10.3390/f9120775
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Conditions and Species Identity Drive Metabolite Levels in Green Leaves and Leaf Litter of 14 Temperate Woody Species

Abstract: Research Highlights: Leaf chemistry is a key driver of litter decomposition; however, studies directly comparing metabolites that are important for tree growth and defence across different woody species are scarce. Background and Objectives: Choosing 14 temperate woody species differing in their growth rates, nutrient demand, shade tolerance, and drought sensitivity, we hypothesized that the species would group according to their metabolite profiles based on their ecological background. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…Trees with high concentrations of polyphenols potentially trigger the diversity of pathotrophic and symbiotrophic fungi (Simon et al, 2018). In addition, higher diversity may be promoted by these tree species because of the low concentration of lignin in their litter, which facilitates nutrient release and allows growth of less-specialized soil fungi (Cotrufo et al, 2015;Paul, 2016).…”
Section: Response Of Fungal Guild Diversities To Tree Economics Spementioning
confidence: 99%
“…Trees with high concentrations of polyphenols potentially trigger the diversity of pathotrophic and symbiotrophic fungi (Simon et al, 2018). In addition, higher diversity may be promoted by these tree species because of the low concentration of lignin in their litter, which facilitates nutrient release and allows growth of less-specialized soil fungi (Cotrufo et al, 2015;Paul, 2016).…”
Section: Response Of Fungal Guild Diversities To Tree Economics Spementioning
confidence: 99%
“…However, in 28 herbal species of the genus Helianthus the specialized metabolomes were correlated with a combination of traits related to the leaf economics spectrum [ 24 ]. Leaf metabolic traits and C/N stoichiometry also change with leaf age and plant development [ 57 ] and may respond to climatic differences between years in a species-specific manner, as shown for deciduous temperate trees [ 58 ]. Further studies are needed to explore such relationships across herbaceous and woody species with shared phylogenies and/or shared environments.…”
Section: Discussionmentioning
confidence: 99%
“…While specialized metabolites may be under a weak evolutionary constraint [ 4 , 61 ], the combination of different metabolites (i.e., the plant metabolomic niche) might be constrained by the plant life-history strategies. The leaf chemistry also affects leaf litter decomposition and nutrient cycling in ecosystems [ 58 ], which should be considered to fully assess impacts of leaf turnover and leaf quality on ecosystems. Further studies are needed to unravel how primary and specialized metabolites as well as leaf structure are affected by environmental challenges in the short-term and how they are interlinked and coordinated with functional adaptations in the long-term under diverse eco-evolutionary scenarios including ongoing climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the important role of phenolic compounds in the decomposition of litter via regulation of soil microbial activity was reviewed [13,61]. A study suggested that soil microbial respiration was significantly inhibited under the warming treatment because the relative abundance of phenolic compounds interferes with microbial metabolism [24].…”
Section: Variations Of Warming-induced Metabolite Responsementioning
confidence: 99%
“…et Wils) were found to significantly decrease [11]. In addition, it was reported that the physiological metabolism of plants was affected by water availability, temperature, and other factors [12][13][14]. Generally, warming alone can increase forest moisture stress [15].…”
Section: Introductionmentioning
confidence: 98%